Chapter 2. The historical geography of an archipelago of polar explorers - Capelotti, P.J. (Septentrio Conference Series, 2015)
An outline of the rationale for a workshop, held in Oslo, Norway, from 12-13 May 2015, to discuss the historic place names of the High Arctic archipelago of Franz Josef Land. The islands contain hundreds of place names that amount to a virtual catalog of polar exploration and explorers of the mid- to late-19th Century. As an example, three American expeditions spent seven years there between 1898-1905, in failed attempts to try to reach the geographic North Pole. However, in the process, they left behind a record of the American Gilded Age that survived even 70 years of Soviet Communism.